Effectiveness of KTP Services in the Sub-District - Purnamasari, Irma; Rahmawati, Rita; Silpiya, Devi; Bani Jafar, Firdaus; Sastrawan, Berry; Fitriah, Maria (Indonesian Association for Public Administration (IAPA), 2023)
E-KTP services at the sub-district level still leave complaints from the public regarding the unsatisfactory service provided, especially service times and service procedures, which still need to be fully understood by the public. This research aims to analyze the effectiveness of E-KTP services at the sub-district level by taking the case of Ciawi District, Bogor Regency, West Java, Indonesia. This research uses a descriptive quantitative approach method, collecting data through observation, interviews, and questionnaires from 41 respondents from the Ciawi District community who were taken by accidental sampling. The research results show data that the effectiveness of E-KTP services in the Ciawi sub-district is considered adequate. This assessment is measured based on three indicators: the source approach with an average value of 3.8, the process approach with an average value of 3.7, and the target approach with an average value of 3.7, from the highest score of 5. However, several areas for improvement in this service still originate from human resource capacity. Therefore, this research recommends that there is a need to increase employee capacity through job training, increasing the knowledge and abilities of officers regarding public services, and improving employee performance.